Inhibitory effects of Japanese horseradish (Wasabia japonica) on the formation and genotoxicity of a potent carcinogen, acrylamide. (24th October 2016) - Shimamura, Yuko; Iio, Misako; Urahira, Tomoko; Masuda, Shuichi
Abstract: BACKGROUND: The formation of acrylamide (AA) in cooked foods has raised human health concerns. AA is metabolized by cytochrome P450 2E1 (CYP2E1) to glycidamide (GA), which forms DNA adducts. This study examined the inhibitory effects of wasabi (Japanese horseradish, Wasabia japonica ) roots and leaves as well as their active component, allyl isothiocyanate (AIT), on the formation and genotoxicity of AA. RESULTS: AA formation (51.8 ± 4.2 µg kg −1 ) was inhibited with ≥2 mg mL −1 of AIT. Wasabi roots also inhibited AA formation (∼90% reduction), but wasabi leaves were not effective at 2 mg mL −1 . Wasabi roots and leaves decreased the number of cells with micronuclei by approximately 33 and 24% respectively compared with the AA treatment group. Moreover, wasabi roots and leaves (100 mg kg −1 body weight (BW) day −1 for each) decreased AA (100 mg kg −1 BW day −1 )‐induced DNA damage. The AA‐induced CYP2E1 activity was decreased by 39 and 26% with wasabi roots and leaves respectively. Further, the activity of glutathione S ‐transferase, which catalyzes the detoxification of AA via glutathione conjugation, increased by 54 and 33% with wasabi roots and leaves respectively. CONCLUSION: These results indicate that wasabi roots and leaves are effective ingredients for inhibiting the formation and genotoxicity of AA. © 2016 Society of Chemical Industry